Creating trust in piranha-infested waters: The confluence of buyer, supplier and host country contexts - Zaheer, Akbar; Kamal, Darcy Fudge (Journal of International Business Studies, 2011)
Research by Dyer and Chu (2000) suggests that trust in exchange varies significantly across borders and influences the level of trust in cross-border exchange dyads. However, while this is a good start, research has yet to develop the concept that not only can the countries of origin of the exchange partners influence the nature and outcomes of dyadic trust but also the country where the exchange dyad is located. Furthermore, such home and host country differences may interact with dyad-level differences in trust creation capabilities and influence trust violation and repair. We develop a framework and propositions along these lines.